Aberrant methylation of cell-free circulating DNA in plasma predicts poor outcome in diffuse large B cell lymphoma. Issue 1 (December 2016) - Kristensen, Lasse; Hansen, Jakob; Kristensen, Søren; Tholstrup, Dorte; Harsløf, Laurine; Pedersen, Ole; De Nully Brown, Peter; Grønbæk, Kirsten
Abstract Background The prognostic value of aberrant DNA methylation of cell-free circulating DNA in plasma has not previously been evaluated in diffuse large B cell lymphoma (DLBCL). The aim of this study was to investigate if aberrant promoter DNA methylation can be detected in plasma from DLBCL patients and to evaluate this as a prognostic marker. Furthermore, we wanted to follow possible changes in methylation levels during treatment. Seventy-four patients were enrolled in the study, of which 59 received rituximab and CHOP-like chemotherapy. Plasma samples were collected from all patients at the time of diagnosis and from 14 healthy individuals used as controls. In addition, plasma samples were collected during and after treatment for surviving patients. In total, 158 plasma samples were analyzed for DNA methylation in the promoter regions ofDAPK (DAPK1 ), DBC1, MIR34A, andMIR34B/C using pyrosequencing. Results Aberrant methylation levels at the time of diagnosis were detected in 19, 16, 8, and 10 % of the DLBCL plasma samples forDAPK1, DBC1, MIR34A, andMIR34B/C, respectively.DAPK1 methylation levels were significantly correlated withDBC1 andMIR34B/C methylation levels (P < 0.001). For the entire cohort, 5-year overall survival (OS) rates were significantly lower in the groups carrying aberrantDAPK1 (P = 0.004) andDBC1 (P = 0.044) methylation, respectively.DAPK1 methylation status were significantly correlated with stage (P = 0.015), as all patients with aberrantDAPK1 methylation were stages III and IV. Multivariate analysis identifiedDAPK1 as an independent prognostic factor for OS with a hazard ratio of 8.9 (95 % CI 2.7–29.3, P < 0.0007). Patients withDAPK1 methylated cell-free circulating DNA at time of diagnosis, who became long-term survivors, lost the aberrant methylation after treatment initiation. Conversely, patients that maintained or regained aberrantDAPK1 methylation died soon thereafter. Conclusions Aberrant promoter methylation of cell-free circulating DNA can be detected in plasma from DLBCL patients and hold promise as an easily accessible marker for evaluating response to treatment and for prognostication. In particular, aberrantDAPK1 methylation in plasma was an independent prognostic marker that may also be used to assess treatment response.